Dual activation of the bile acid nuclear receptor FXR and G-protein-coupled receptor TGR5 protects mice against atherosclerosis. - Shinobu Miyazaki-Anzai; Masashi Masuda; Moshe Levi; Audrey L Keenan; Makoto Miyazaki (PLoS ONE, 2014)
Bile acid signaling is a critical regulator of glucose and energy metabolism, mainly through the nuclear receptor FXR and the G protein-coupled receptor TGR. The purpose of the present study was to investigate whether dual activation of FXR and TGR5 plays a significant role in the prevention of atherosclerosis progression. To evaluate the effects of bile acid signaling in atherogenesis, ApoE-/- mice and LDLR-/- mice were treated with an FXR/TGR5 dual agonist (INT-767). INT-767 treatment drastically reduced serum cholesterol levels. INT-767 treatment significantly reduced atherosclerotic plaque formation in both ApoE-/- and LDLR-/- mice. INT-767 decreased the expression of pro-inflammatory cytokines and chemokines in the aortas of ApoE-/- mice through the inactivation of NF-κB. In addition, J774 macrophages treated with INT-767 had significantly lower levels of active NF-κB, resulting in cytokine production in response to LPS through a PKA dependent mechanism. This study demonstrates that concurrent activation of FXR and TGR5 attenuates atherosclerosis by reducing both circulating lipids and inflammation.